A Randomized Study of Lung Cancer Screening with Spiral Computed Tomography: Three-year Results from the DANTE Trial - Infante, Maurizio; Cavuto, Silvio; Lutman, Fabio Romano; Brambilla, Giorgio; Chiesa, Giuseppe; Ceresoli, Giovanni; Passera, Eliseo; Angeli, Enzo; Chiarenza, Maurizio; Aranzulla, Giuseppe; Cariboni, Umberto; Errico, Valentina; et al. (American journal of respiratory and critical care medicine, 2009)
Screening for lung cancer with modern imaging technology may decrease lung cancer mortality, but encouraging results have only been obtained in uncontrolled studies. To explore the effect of screening with low-dose spiral computed tomography (LDCT) on lung cancer mortality. Secondary endpoints are incidence, stage at diagnosis, and resectability. Male subjects, aged 60 to 75 years, smokers of 20 or more pack-years, were randomized to screening with LDCT or control groups. All participants underwent a baseline, once-only chest X-ray and sputum cytology examination. Screening-arm subjects had LDCT upon accrual to be repeated every year for 4 years, whereas controls had a yearly medical examination only. A total of 2,811 subjects were randomized and 2,472 were enrolled (LDCT, 1,276; control, 1,196). After a median follow-up of 33 months, lung cancer was detected in 60 (4.7%) patients receiving LDCT and 34 (2.8%) control subjects (P = 0.016). Resectability rates were similar in both groups. More patients with stage I disease were detected by LDCT (54 vs. 34%; P = 0.06) and fewer cases were detected in the screening arm due to intercurrent symptoms. However, the number of advanced lung cancer cases was the same as in the control arm. Twenty patients in the LDCT group (1.6%) and 20 controls (1.7%) died of lung cancer, whereas 26 and 25 died of other causes, respectively. The mortality benefit from lung cancer screening by LDCT might be far smaller than anticipated.